Corruption in Asia Pacific business organizations: insights on causes, conditions, consequences and treatment. Issue 4 (8th August 2019) - Andrews, Tim G.; Rowley, Chris; Nimanandh, Khongphu; Buranapin, Siriwut
ABSTRACT: In the wake of the 1997 Asian financial crisis a wave of articles and commentaries focused increasingly on the so-called 'dark side' of Asian business. At the forefront of these lay investigations into the deleterious effects of corruption on economic development, business performance and international investor confidence. In subsequent years, due in part to converging pressures for universal corporate standards, the flow of research declined on the (implicit) assumption that corruption was a decreasing problem as new generations of Asian managers assimilated 'Western' values and practices. However, despite continuing admonishments and initiatives, the effects of corrupt practice at all levels remains as entrenched and as serious as ever. Blending micro and macro-level analysis along with both conceptual and empirical investigations, this collection offers some of the most recent frameworks and findings to explain the causes, conditions, consequences and treatment of corruption in 21 st century Asia.